2018
DOI: 10.1002/cctc.201800971
|View full text |Cite
|
Sign up to set email alerts
|

Rhodamine 6G Radical: A Spectro (Fluoro) Electrochemical and Transient Spectroscopic Study

Abstract: A detailed study on the radical of rhodamine 6G, a key intermediate in photoredox catalysis, is presented. Various methods of its preparation (photoinduced electron transfer, electrochemistry), its spectroscopic characterization, stability, oxidation, photoionization and transient spectroscopic study have been investigated. Photooxidation of reduced rhodamine 6G has been established as a sensitive method for determination of dissolved oxygen. Photoionization of rhodamine 6G radical was found to be strongly sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 85 publications
1
24
0
Order By: Relevance
“…4b. This substrate is energetically not expected to undergo bond cleavage by the excited radical R˙*, as the reduction potential necessary amounts to –2.9 V vs. SCE 45. Indeed, in Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…4b. This substrate is energetically not expected to undergo bond cleavage by the excited radical R˙*, as the reduction potential necessary amounts to –2.9 V vs. SCE 45. Indeed, in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Addition of a reducing agent, ascorbic acid, promotes formation of the rhodamine radical from either the singlet or the triplet state. Since Rh6G in water is cationic,45 electron transfer from the reducing agent will form the neutral Rh6G radical R˙. This radical is characterised by a certain lifetime, and will ultimately relax to the cationic ground state by shedding the additional electron to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the widely used Ir­(ppy) 3 complex is capable of reducing aryl iodides and bromides, but aryl chlorides are out of range and require multiphoton excitation processes when using visible photons . In 2014, the interest in two-photon approaches received a boost by the discovery of novel mechanisms , with far-reaching laboratory applications for reductive transformations, in organic solvents and water. Given that intense irradiation is required for two-photon mechanisms to be efficient, the availability of cheap light sources with high photon fluxes such as high-power LEDs and cw lasers laid the grounds for the ongoing rapid development in that research field.…”
Section: Introductionmentioning
confidence: 99%
“…The excited state of Rh6G + has previously been reported to be quenched by DIPEA via electron transfer from DIPEA to the excited dye molecule with a quenching constant k DIPEA = 4.41 × 10 9 M −1 s −1 (i.e., Stern−Volmer constant K DIPEA = 15.85 M −1 ). 6 To study the effects of competitive fluorescence quenching of Rh6G + by N-MP and DIPEA, typical concentrations used in synthetic reactions are considered (i.e., [N-MP] = 1 M and [DIPEA] = 0.147 M). 4 The average fluorescence lifetime of Rh6G + is reduced to 0.92 ns when N-MP is added and 1.79 ns in the case of DIPEA (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also suggested that an excited Rh6G • ejects an unpaired electron into the solvent, and the resulting solvated electron then reduces the aryl halide substrate. 6,7 The resulting anion radical [Ar-X] •− undergoes mesolysis of the C−X bond to yield an aryl radical Ar • that reacts with N-MP to form the cross-coupling product (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%